2013
DOI: 10.1083/jcb.201306036
|View full text |Cite
|
Sign up to set email alerts
|

The midbody ring scaffolds the abscission machinery in the absence of midbody microtubules

Abstract: The septins, but not midbody microtubules, are important for daughter cell cytoplasmic isolation and ESCRT-dependent midbody ring release during abscission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 57 publications
(96 reference statements)
11
90
1
1
Order By: Relevance
“…Similarly, it has been reported that the four MBRs of the Q neuroblast lineage are phagocytosed by macrophages in vivo in C. elegans larvae (Chai et al, 2012). By contrast, it has been suggested that the MBR of the first cell division in C. elegans embryos retracts and is released into the posterior cell following an ESCRT-dependent abscission step (Green et al, 2013). However, very recent observations indicate that the MBR is actually engulfed after abscission (Ou et al, 2014;Singh and Pohl, 2014).…”
Section: Midbody Remnant Engulfment Involves Cell Surface Receptorsmentioning
confidence: 86%
“…Similarly, it has been reported that the four MBRs of the Q neuroblast lineage are phagocytosed by macrophages in vivo in C. elegans larvae (Chai et al, 2012). By contrast, it has been suggested that the MBR of the first cell division in C. elegans embryos retracts and is released into the posterior cell following an ESCRT-dependent abscission step (Green et al, 2013). However, very recent observations indicate that the MBR is actually engulfed after abscission (Ou et al, 2014;Singh and Pohl, 2014).…”
Section: Midbody Remnant Engulfment Involves Cell Surface Receptorsmentioning
confidence: 86%
“…This second steps relies on septins and the endosomal sorting complex required for transport (ESCRT) machinery. Strikingly, this study also found that midbody microtubules are dispensable for both steps, raising the possibility that the midbody ring itself, but not the midbody microtubules are crucial for abscission, as seen in embryos that have been depleted of the microtubule bundling protein SPD-1 (also known as PRC1 in mammals) (Green et al, 2013). Furthermore, the cell-cell interface between daughter cells remains firmly closed in embryos that lack midbody complexes between the mitotic cell and its neighbours at the cleavage furrow (B9 and B0), followed by the assembly of new E-cadherin complexes at the daughter-daughter interface (dark green, C9).…”
Section: En Route To Abscission -The Final Cutmentioning
confidence: 88%
“…microtubules or are depleted of ESCRT proteins or septins (Green et al, 2013;Maddox et al, 2007), whereas these conditions cause defective abscission and multinucleation in isolated mammalian cells (Caballe and Martin-Serrano, 2011;Estey et al, 2010;Mollinari et al, 2005). Thus, at least in worms, redundant mechanisms might contribute to the formation of a stable cellcell interface and make this cytokinetic mechanism unique.…”
Section: En Route To Abscission -The Final Cutmentioning
confidence: 99%
See 1 more Smart Citation
“…132 The midbody ring is thought to act as a scaffold platform for recruiting and/ or activating signaling proteins that contribute to the regulation of abscission and post-mitotic cell fate. [133][134][135] Proteomics and cell biology studies have indicated that a large number of proteins (>100) locate to the midbody ring itself or to flanking regions within the intracellular bridge. 44,136 The molecular details of the role of these proteins, and the interaction between pathways involved in the abscission process, are only starting to emerge.…”
Section: Membrane Abscission Formation Of Midbodymentioning
confidence: 99%